Consumer Protection in Shopee Coin Conversion Services on Application X: An Analysis Based on Maqasid al‑Shariah - Tedy Rahardi, Mohamad; Sail Arbiah Br. Saragi, Salisa; Ilham, Muhammad (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
This research is prompted by the proliferation of Shopee coin conversion services on the X (Twitter) application, which are highly susceptible to fraudulent activities. These transactions involve third parties informally, operating without any official protection or supervision from Shopee. The primary objectives of this study are to understand the service mechanism, evaluate legal protections for defrauded consumers, and assess the practice through the hifz al-mal (protection of wealth) principle within the maqashid sharia framework. Utilizing an empirical qualitative method, the findings reveal that these services exploit limitations on coin usage and remain high-risk due to a lack of adequate legal guarantees. While normative protection is available under the Consumer Protection Law and the ITE Law, implementation remains ineffective due to weak responses from law enforcement and widespread consumer pessimism. From a maqashid sharia perspective, this practice contradicts the hifz al-mal principle as it fails to ensure the secure, fair, and transparent protection of consumer assets.